2001
DOI: 10.1074/jbc.m101382200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Determinants That Are Important in the Assembly of N-Methyl-d-aspartate Receptors

Abstract: To determine which domains of the N-methyl-D-aspartate (NMDA) receptor are important for the assembly of functional receptors, a number of N-and C-terminal truncations of the NR1a subunit have been produced. Truncations containing a complete ligand binding domain bound glycine antagonist and gave binding constants similar to those of the native subunit, suggesting they were folding to form antagonist binding sites. Since NR2A is not transported to the cell surface unless it is associated with NR1 (McIlhinney, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
99
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 40 publications
10
99
4
Order By: Relevance
“…Assembly-Several studies have suggested a role for the X domain in the assembly of multimeric channels (10,12,32,33). Furthermore, experiments performed with separately expressed extracellular domains of GluR-D subunit indicate that the X domain is able to form dimers, consistent with a role in the assembly (11).…”
Section: Discussionmentioning
confidence: 57%
“…Assembly-Several studies have suggested a role for the X domain in the assembly of multimeric channels (10,12,32,33). Furthermore, experiments performed with separately expressed extracellular domains of GluR-D subunit indicate that the X domain is able to form dimers, consistent with a role in the assembly (11).…”
Section: Discussionmentioning
confidence: 57%
“…Both the LIVBP and mGluR1-NTD fold into a structure containing two lobes, where each lobe is formed by two alternating regions of the primary amino acid sequence (12,23). Unlike LIVBP, the mGluR1-NTD assembles in dimers (at the level of lobe-1), a feature that fits with the proposed predominant dimeric organization of the iGluR-NTD (9,10,24), and therefore was chosen as the primary alignment template. Nonetheless, the structure of the S1S2 glutamate-binding domain was also considered, because, like the mGluR1-NTD (which is the glutamate-binding domain in mGluRs), S1S2 folds in a bi-lobed structure, also formed by alternating regions, and it associates primarily in dimers (3,21).…”
Section: Glur3/glur6mentioning
confidence: 99%
“…Each subunit of the receptor is organized into domains with an extracellular aminoterminal domain (ATD) 2 and ligand-binding domain (LBD), the transmembrane, pore-forming region, and the intracellular carboxyl-terminal domain. The ATDs of glutamate receptors are known to be involved in receptor assembly and in controlling the open probability of the receptor (1)(2)(3). Specifically, receptors composed of GluN1-GluN2A subunits exhibit a higher channel open probability than those composed of GluN1-GluN2B subunits (4,5).…”
mentioning
confidence: 99%